Development of the fundamental power coupler for 324 MHz superconducting cavities - Mengxu Fan; Huachang Liu; Xiaolei Wu; Yao Yang; Shunming Liu; Ahong Li; Yun Wang; Bo Li; Peihua Qu; Qiang Chen; Sheng Wang (Physical Review Accelerators and Beams, 2023)
The China Spallation Neutron Source upgrade project (CSNS-II) has completed the preliminary design report and is expected to start in the fall of 2023. It plans to add two types of superconducting cavities: the 324-MHz double spoke superconducting cavity and the 648-MHz elliptical superconducting cavity in the linac section of the accelerator to upgrade the beam power from 100 to 500 kW, requiring more than 40 new fundamental power couplers (FPCs). These couplers will operate at pulse mode with a peak power ranging from 100 to 380 kW. To master the entire R&D process of the FPC for superconducting cavities, meanwhile, provide the horizontal test condition for various superconducting cavities research, a pair of 324-MHz power couplers for the double spoke superconducting cavity are developed. This coupler is a coaxial structure with a disk-warm ceramic window, and its characteristic impedance is 50  Ω. Multiphysics design is performed to ensure that the coupler meets the actual requirements. Structures of the coupler are optimized to realize a clean assembly with the cavity in Class 10 clean room and avoid window failure due to the bombardment of electrons generated by possible cavity field emission. We have successfully fabricated two FPCs and high power conditioned them on the test bench at room temperature. The test results show that FPCs can transmit a peak radio frequency (rf) power of 2 MW with a duty factor of 1.625% in traveling wave mode and an rf power of 500 kW with a duty factor of 3% in standing wave mode with arbitrary reflection wave phase. It meets the requirement of spoke cavities for CSNS-II—200 kW maximum power with a duty factor of 3%. Multipacting (MP) zones found during the high-power conditioning agree reasonably well with those predicted by simulations.